2015
DOI: 10.1007/s13280-014-0601-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping bundles of ecosystem services reveals distinct types of multifunctionality within a Swedish landscape

Abstract: Ecosystem services (ES) is a valuable concept to be used in the planning and management of social–ecological landscapes. However, the understanding of the determinant factors affecting the interaction between services in the form of synergies or trade-offs is still limited. We assessed the production of 16 ES across 62 municipalities in the Norrström drainage basin in Sweden. We combined GIS data with publically available information for quantifying and mapping the distribution of services. Additionally, we ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
165
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(195 citation statements)
references
References 29 publications
25
165
2
3
Order By: Relevance
“…In our study, we identified five bundles that were strongly linked to the LULC trajectories that we employed for the ES trend mapping. For terminology we relied, where possible, on previously published work to facilitate comparison between the different studies (Turner et al 2014;Queiroz et al 2015;Yang et al 2015).…”
Section: Ecosystem Service Bundlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we identified five bundles that were strongly linked to the LULC trajectories that we employed for the ES trend mapping. For terminology we relied, where possible, on previously published work to facilitate comparison between the different studies (Turner et al 2014;Queiroz et al 2015;Yang et al 2015).…”
Section: Ecosystem Service Bundlesmentioning
confidence: 99%
“…Knowing whether the presence of a specific ES bundle excludes the presence of another bundle or identifying ecosystems where multiple services are likely to coexist, will be an essential advantage for landscape management and for promoting the importance of landscape functions to policy makers and society (Crouzat et al 2015). Some of the most significant studies in recent years in this context include ES pattern analysis in Denmark by Turner et al (2014), spatiotemporal analysis of ES bundles at the municipality level by Renard et al (2015) in the greater Montreal region (Canada) and the analysis of Queiroz et al (2015) on the multi-functionality of Swedish landscapes. All these studies aim to identify ES patterns based on the underlying socioecological subsystems and the specific LULC composition.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the correlation coefficient indicates the extent to which the pairs of services appear in the same location. Another method is to use principal component analysis (PCA) of quantified ecosystem service counts in multiple land units to identify strong correlates of the principal components, followed by cluster analysis of the results (Raudsepp-Hearne et al, 2010;Plieninger et al, 2013;Turner et al, 2014;Queiroz et al, 2015). Multiple correspondence analysis (MCA) can also be (2012) identified three bundles of ecosystem services for urban populations, rural people in multifunctional landscapes, and provisioning services related to food (agriculture and fishing).…”
Section: Physical Landscape Associations With Ecosystem Service "Bundmentioning
confidence: 99%
“…In Norway, Hausner et al, (in press) reported ecosystem service bundles related to cognitive meanings of landscapes and bundles associated with historical rights to provisioning services in land tenures. And in Sweden, Queiroz et al, (2015) found multifunctional ecosystem service bundles in human-dominated landscapes, while densely populated urban areas were hotspots for cultural services. In this study, we first analyze the Norwegian spatial data for the presence of ecosystem value bundles, and then examine whether these bundles are spatially associated with land cover.…”
Section: Physical Landscape Associations With Ecosystem Service "Bundmentioning
confidence: 99%
“…By attributing value to a biophysical structure or process, people become involved in the transformation of biophysical structures or processes to ecosystem services (Spangenberg 2014). As these services are co-produced by both humans and nature, it therefore has an intrinsically social-ecological character (Andersson et al 2007;Reyers et al 2013;Queiroz et al 2015). The ecosystem cascade framework of Haines-Young and Potschin (2010) is useful in analysing the ecosystem services wild bees mediate.…”
Section: Introductionmentioning
confidence: 99%